The Position of Women in International Relationship: A Book Review Gender & Hubungan Internasional, Ani Seotjipto, Jalasutra Bandung, 2013, 320 pages, ISBN 978-602-825-293-5 - Tastama, Ridho Dwiky (Faculty of Law, Universitas Negeri Semarang, 2019)
This book also includes various forms of examples of statements of international agreements between countries such as: Singapore Declaration of 1992, Scale of Assessments, Rule of Procedure of the General Assembly, Resolution 1514 (XV): Declaration on the Granting of Independence to Colonial Countries and Peoples, Resolution 1514 (XV): Principles Which Should Be a Guide for Determining whether or not An Obligation Existence to Information of the Charter of the United Nations, and Declaration of Principles of International Law Concerning Friendly Relations and Co-operation among States in Accordance with the Charter of the United Nations. This book explains how to look at international relations in terms of gender as well as feminism, mostly in this book discussing women and their human rights in international relations in the world. The author wrote this book based on his perspective as a subject of women's law to international law. This book uses language that is easily understood and understood by students so it is very helpful in learning activities and very helpful in giving references in making lectures related to international relations.